THE DYNAMICS OF INTERNET-BASED MULTINATIONAL CORPORATIONS IN CHINA: YAHOO! CHINA CASE - Rafsyanjani Mohammad (UNIDA GONTOR, 2018)
Abstract This paper aims to analyze the dynamics of internet-based multinational companies in China with a special focus on the discussion of the factors behind the closure of Yahoo! Inc.’s business operations in China by 2015. In order to answer this research question, this paper uses a qualitative method based on literature study as a research method. Based on the theoretical approach offered by obsolescing bargain theory and Porter's five forces model, this research conclude that the Yahoo! Inc.’s withdrawal from the Chinese market due to the accumulation of the increasingly stringent Chinese Government regulation on the internet and the increasingly competitive domestic internet industry. Strict regulation is representation of the